The dynamic genome of Hydra - Chapman, Jarrod A.; Simakov, Oleg; Balasubramanian, Gnana Prakash; Bertulat, Bianca; Guder, Corina; Nakamura, Yukio; Özbek, Suat; Watanabe, Hiroshi; Holstein, Thomas W. (Nature, 2010)
Nature is the international weekly journal of science: a magazine style journal that publishes full-length research papers in all disciplines of science, as well as News and Views, reviews, news, features, commentaries, web focuses and more, covering all branches of science and how science impacts upon all aspects of society and life.
Gesehen am 16.02.2017